Effect of long-term treatment with low doses of the LHRH antagonist Cetrorelix on pituitary receptors for LHRH and gonadal axis in male and female rats - Horvath, Judit E. (National Academy of Sciences, 2004)
Our previous studies showed that treatment of female rats with large doses of Cetrorelix, an antagonist of luteinizing hormone-releasing hormone (LHRH), reduces levels of serum LH, estradiol, progesterone, and the concentration of pituitary LHRH receptors (LHRH-Rs) and their mRNA expression. Serum LH and testosterone levels and pituitary LHRH-R in male rats are also decreased by high doses of Cetrorelix. This approach can be used for therapy of sex hormone-dependent cancers. However, in conditions where an incomplete hormone deprivation is indicated, lower doses of Cetrorelix may suffice. Thus, we investigated the effect of a 30-day treatment with a low-dose depot formulation of Cetrorelix (20-24 μg per kg per day) on the pituitary-gonadal axis of male and female rats. In both sexes, lower serum LH levels were observed on day 4 after administration. In males, LH returned to control levels by day 10, whereas in females, a rebound LH elevation occurred. Testosterone levels in male rats were decreased up to day 20, but on day 30, the values were similar to controls. In females, serum estradiol was reduced on day 4; however, by day 10 it returned to normal. Progesterone levels were diminished through the entire period. Female rats showed diestrous smears during the first week of treatment and prolonged estrous periods thereafter. The weights of testes and ovaries were significantly lower, but not the weights of prostate, seminal vesicles, and uterus. Pituitary LHRH-R mRNA and LHRH-R protein levels were not significantly different from the controls. Thus, the treatment with low doses of Cetrorelix did not seriously impair gonadal functions. The results suggest that Cetrorelix in low doses induces only a partial pituitary-gonadal inhibition and might be indicated for treatment of endometriosis, leiomyomas, and benign prostatic hyperplasia.